INTERAKSI ISLAM DENGAN BUDAYA BANJAR - Abdul Wahab Syahrani; Muhammad Salman Ramadhani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
In South Kalimantan, what are commonly referred to as Banjar people are the (native) residents of the area around the city of Banjarmasin (the area of Sungai Jingah, Kuin and Kampung Melayu). This area extends to the city of Martapura, the capital of Banjar district and the surrounding area. The language used by the Banjar people is the Banjarese language. Before Islam entered the island of Borneo, the inhabitants had embraced the Hindu-Buddhist religion or embraced the Kaharingan belief, which of course was very different from the teachings of Islam. Although the process of Islamization of the people of Kalimantan continues to this day through da'wah and education, the traces of previous religious beliefs and culture cannot be completely erased so that some of them still influence the diversity and culture of Muslims to this day.